Mindfulness-Based Interventions for acute state of mental disorders: An integrative review (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This integrative review aimed to analyze the characteristics of Mindfulness-Based Interventions for patients diagnosed with mental disorders in an acute state. Empirical articles published in the Web of Science, Embase, PubMed/MEDLINE and BVS databases were selected and data collection was performed by two independent judges. The 18 empirical articles collected included 645 participants and were analyzed according to three broad aspects: level of formality; type of approach; and object of stimulated perception. Most interventions were conducted in hospital settings, with groups of adult patients with psychotic symptoms. The intervention protocols had a predominantly experiential character, with formal practices focused on stimulating interoception and private events. The benefits of psychoeducation, informal mindfulness practices, and the stimulation of different objects of perception are discussed.
Keywords: Mindfulness; Mental health; Severe mental disorders; Crisis intervention; Integrative review